Fruiting and artificial maturation induction with 2-chloroethylphosphonic acid at different stages for ‘roxo de valinhos’ figs - Capellesso, Adinor José; Zanardi, Aquidauana Miqueloto; Bazi, Claudinei; Züge, Anderson André (Revista de Ciências Agroveterinárias, 2023)
The Brazilian production of Ficus carica L., particularly ’Roxo de Valinhos’ figs variety, is predominantly concentrated from January to March. The ethylene utilization to anticipate and standardize fig harvesting has the potential to alter the supply and improve economic results. The objective of this study was to establish a growth curve and evaluate the effect of 2-chloroethylphosphonic acid (ethephon) on the maturation and quality of ’Roxo de Valinhos’ figs at different periods, measured in days after effective fruit set (DAEFS). The study was divided into two concurrent experiments conducted in a commercial orchard in Linha Jacutinga, a village in São Miguel do Oeste, SC, during the 2020/2021 harvest. In each experiment was used randomized block design, with eight replications (blocks), with the plant as the block and two basal fruits of a branch as the experimental unit. Experiment I consisted of characterizing the natural development of figs at different stages. The analyses of pseudo-fruits included measurements of mass, diameter, length, color, texture, soluble solids, and titratable acidity. Experiment II consisted of an application of ethephon 500 µL L-1 at 10, 20, 30, 40, 50, 60, 70 and 80 DAEFS. The control treatment was natural development without any applications. Harvesting took place when the figs showed the presence of purple coloration, indicating ripeness. The figs were evaluated for their physical and chemical attributes. The growth behavior followed a double-sigmoid curve with three stages of development. The applications of ethephon at 500 µL L-1 did not promote the desired responses for artificial maturation induction until 50 DAEFS. Satisfactory results began at 60 DAEFS, with a diameter of ≥ 39.8 mm, and at 70 DAEFS, with a diameter of ≥ 38.1 mm. However, 95% of desirable responses for maturation by artificial induction occurred at 80 DAEFS when figs had an average diameter of 37.3 ± 1.8 mm.